PEDAGOGICAL FRAMEWORK CONDITIONS TO PROMOTE THE ARTISTIC ACTIVITIES IN PRESCHOOL - Randoha, Antra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The pedagogical process in preschool is based on children ascomprehensive personality’s development, using extensive pedagogic educational and learning methods. Preschool methodology includes very wide range both ofknowledge, ability and skills development ensuring. Preschool child is an individual with only his own typical characteristics, aptitudes and abilities, therefore the pedagogical process must be especially well-considered, with selected necessary materials, forms of training and education, to be able to contribute to the development of the whole individual with an emphasis on self development of preschooler in the process of pedagogical – artistic activity. The artistic activity in preschool significantly affects child development process therefore it is important to follow in process the pedagogical conditions of the artistic activity’s promotion.